Chronic Mastocytosis. Case Report and Literature Review - Iraima Mayón Moya; Danibys Garcell Peña; José Manuel Peraza Ramos (Revista Finlay)
Chronic cutaneous mastocytosis is a genodermatosis of unknown etiology and that is within the group of rare or infrequent diseases. They are characterized by the growth and accumulation of mast cells in the skin and other organs of unknown cause and manifest as urticaria pigmentosa. The case of a male patient is presented, with erythematopapular lesions in the region of the hands that spread to the entire body and scalp that, when they disappeared, left hyperchromic spots with Darier's sign: positive. The diagnosis of urticaria pigmentosa was confirmed by skin biopsy. It is a rare disease with a low incidence, the cutaneous form has a favorable prognosis, so it is of vital importance to know and diagnose this entity early with a multidisciplinary management to prevent the systemic manifestations that appear. Taking a symptomatic treatment will allow a better quality of life in infants. The case is presented because mastocytosis is considered a rare disease, the prevalence and incidence of these cases is very low.